The K-State emoji scale: development and validation - Deubler, Grace Isabella (Kansas State University, 2019)
Emoji have grown in popularity as a method for digital communication. In recent years, there has been increased interest in the connection between emoji and emotional response to consumer products. Research has been conducted linking emoji and the emotional response from food stimuli in adults via avenues such as Twitter, and in children. The objective of the research discussed in this thesis was to create, validate, and determine suitability of an emoji-based scale for measuring consumers’ emotional response to products. First, an online study was conducted to assess the application of an emoji-based pictorial facial scale with children ages 8–11 (grades 3rd, 4th, and 5th). Two hundred and fourteen participants were asked to evaluate their liking and emotional response using the Peryam and Kroll (P&K) scale (super good/super bad) and pictorial emoji scale, respectively, for both food and non-food experiences. Scores from each grade level were not statistically different. The responses from both scales had similar mean scores and distribution patterns for all experiences with no incidence of bias toward any one emoji. These findings support the suitability of the emoji scale for measuring emotional response using written stimuli names with children ages 8–11 in the United States and indicate it is a reasonable alternative to the P&K scale for this demographic. Following the online study, a two-phase project was carried in the US and China with children ages 8-11. In Phase 1, participants were asked to evaluate written food and situational stimuli using one of two emoji scale prototypes and the Peryam & Kroll (P&K) scale (super good/super bad). One prototype, the K-State emoji scale, performed significantly better than the other based on its stimuli discrimination and participant understanding and was chosen for further research. In Phase 2, the same demographic was asked to taste and evaluate flavored potato chip samples using both the K-State emoji scale and P&K scale. Participants in each country used the emoji scale in a similar manner and the scale was able to discriminate across stimuli. The results demonstrated the K-State emoji scale is valid in the United States and China and is suitable for measuring children’s emotional response to products. In a separate study, experiments using 299 flavored potato chip consumers in the US and China were conducted to understand the suitability of the K-State emoji scale for measuring adult consumers’ emotional response to food products. Adults in each country were asked to evaluate five different flavored potato chips using a traditional 9-point hedonic scale and the K-State emoji scale. The K-State emoji scale was found to be as equally discriminating as the 9-point scale. The scoring from the two scales followed similar distribution patterns and were highly correlated. When asked about the K-State emoji scale’s appropriateness for evaluating the flavored potato chips, a higher number of participants in China felt it was “appropriate” or “very appropriate” for the task compared to participants in the US. The K-State emoji scale is applicable in both countries, however, may be better received by the Chinese adult consumer. The findings in this thesis demonstrate the potential of the K-State emoji scale. The scale has shown promising results in both the US and China with children and adults. The new method would allow for easier research across cultures as the scale is visual and requires no translation. Considering the surge in emoji usage, the scale is both topical and provides additional justification for the use of emoji in research.
Keywords: Consumer Research; Children; Emotion; Emoji; Scale